Oxford practice tests for the TOEIC test (Oxford University Press, 2000)
This is a Practice tests for the TOEIC test. Lin Lougheed is a well-known ELT figure with particular expertise in writing prep courses for TOEIC. He has written Oxford Practice Tests for the TOEIC Test for OUP, as well as numerous TOEIC preparation texts and skills materials for other publishers.